2017
DOI: 10.5812/ijpbs.7431
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Beta and Alpha Neurofeedback on Memory: A Randomized, Double-Blind, Sham-Controlled, Clinical Trial

Abstract: Background: Neurofeedback training is a promising area of research in cognitive performance. Although diverse patterns of frequency in improving memory performance have been studied, beta up-training and low alpha/high alpha ratio suppression have not yet been studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…The most common protocol found for enhancing working memory was the up-regulation of Alpha power rhythm (Hsueh et al, 2016; Pei et al, 2018; Wei et al, 2017). The second most common protocol is Beta and Alpha rhythm (Farnia et al, 2017; Jirayucharoensak et al, 2019), which can be followed by low alpha/high alpha ratio suppression (Farnia et al, 2017). Alpha and theta (Reis et al, 2016) and SMR rhythm (Campos da Paz et al, 2018) up-regulation protocols were also found to WM improvement.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The most common protocol found for enhancing working memory was the up-regulation of Alpha power rhythm (Hsueh et al, 2016; Pei et al, 2018; Wei et al, 2017). The second most common protocol is Beta and Alpha rhythm (Farnia et al, 2017; Jirayucharoensak et al, 2019), which can be followed by low alpha/high alpha ratio suppression (Farnia et al, 2017). Alpha and theta (Reis et al, 2016) and SMR rhythm (Campos da Paz et al, 2018) up-regulation protocols were also found to WM improvement.…”
Section: Resultsmentioning
confidence: 99%
“…Although EEG-NFB received critiques for the poor description of protocols in the past (Vernon-et al, 2004), the researches of the past 6 years have shown an improvement on this methodological aspect since non-specific factors and placebo effects are taken more into account through SHAM groups (Campos da Paz et al, 2018; Engelbregt et al, 2016; Farnia et al, 2017; Gadea et al, 2016; Jirayucharoensak et al, 2019; Jurewicz et al, 2018; Mehran et al, 2015; Reis et al, 2016; Wei et al, 2017). Moreover, the modality of feedback, type of reward, number and placement of electrodes, and duration and number of sessions were carefully described, and this is considered a positive methodological aspect.…”
Section: Discussionmentioning
confidence: 99%
“…The results indicate a positive effect of the alpha NFT on memory. In addition, the control groups of most included studies (9 of 14 WM studies and 4 of 6 EM studies) (1 study with active neurofeedback (Pei et al, 2018), 2 studies with sham neurofeedback (Guez et al, 2014;Xiong et al, 2014), or 8 studies with silent feedback (Escolano et al, 2011;Lecomte and Juhel, 2011;Zoefel et al, 2011;Alekseeva et al, 2012;Reis et al, 2016;Farnia et al, 2017;Gordon et al, 2019;Naas et al, 2019) showed no memory change. Two active control groups showed significant improvement in WM and EM after training (Hsueh et al, 2016;Wei et al, 2017), and the alpha group of the two studies exhibited significant enhancement of WM and EM compared with the active control group.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, this protocol is quite appealing to the healthy population who would likely be the main initial users of multiuser neurofeedback. Alternatively, the frontal cortex has also been used for improving cognitive performances (Farnia et al 2017). While frontal locations have the advantage of better contact between the electrode and skin as typically this area has no hair, they are more prone to artifacts due to eye movement, blinking, and facial muscle activity.…”
Section: Discussionmentioning
confidence: 99%